MATURITY GRADING KEY OF MESODESMA DONACIUM (BIVALVIA, MESODESMATIDAE) - Perea, Ángel (2015)
The new maturity grading key for Mesodesma donacium (Lamarck, 1818) was made, reducingthe subjectivity in determining the stages of the gonadal maturity. The aim of this study was todescribe the scale of gonadal maturity of the species, both females and males. Six stages were considered: Virginal (0), at rest (I), in maturation (II), mature (III), spawning / expelling (IV), recovery / post expelling (V). Differences of this grading key with those made previously are discussed.